Modification of crystal anisotropy and enhancement of magnetic moment of Co-doped SnO2 thin films annealed under magnetic field - Loya-Mancilla, Sagrario M.; Poddar, Pankaj; Das, Raja; Ponce, Hilda E. Esparza; Templeton-Olivares, Ivan L.; Solis-Canto, Oscar O.; Ornelas-Gutierrez, Carlos E.; Espinosa-Magaa, Francisco; Olive-Mendez, Sion F. (Nanoscale Research Letters, 2014)
Co-doped SnO2 thin films were grown by sputtering technique on SiO2/Si(001) substrates at room temperature, and then, thermal treatments with and without an applied magnetic field (H-TT) were performed in vacuum at 600 degrees C for 20 min. H-TT was applied parallel and perpendicular to the substrate surface. Magnetic M(H) measurements reveal the coexistence of a strong antiferromagnetic (AFM) signal and a ferromagnetic (FM) component. The AFM component has a N,el temperature higher than room temperature, the spin axis lies parallel to the substrate surface, and the highest magnetic moment m =7 mu(B)/Co at. is obtained when H-TT is applied parallel to the substrate surface. Our results show an enhancement of FM moment per Co+2 from 0.06 to 0.42 mu(B)/Co at. for the sample on which H-TT was applied perpendicular to the surface. The FM order is attributed to the coupling of Co+2 ions through electrons trapped at the site of oxygen vacancies, as described by the bound magnetic polaron model. Our results suggest that FM order is aligned along [101] direction of Co-doped SnO2 nanocrystals, which is proposed to be the easy magnetization axis.
Keywords: Antiferromagnetism; Crystal anisotropy; Diluted magnetic oxide; Ferromagnetism; Magnetic anisotropy; Magnetic moment; Spin axis; thin film

Polycrystalline MnGe2 thin films on InAs(001) substrates - Gutierrez-Naranjo, David; Holguin-Momaca, Jose T.; Solis-Canto, Oscar O.; Gupta, Preeti; Poddar, Pankaj; Espinosa Magana, Francisco; Olive-Mendez, Sion F. (Thin Solid Films, 2018)
We report on the growth of MnGe2 thin films on InAs(001) substrates using radio frequency-magnetron cosputtering. Polycrystalline thin films were obtained at a substrate temperature of 353 K. X-ray diffractometry was used to identify the tetragonal MnGe2 phase (space group 14/mcm). Measurements of the magnetic field and temperature dependence of the magnetization revealed that the MnGe2 thin films are ferromagnetic with a magnetization of 280 kAm(-1) and a Curie temperature of 62 K. Additionally, an antiferromagnetic component is observed at low temperatures, which may arise atomic disorder at the grain boundaries between MnGe2 crystallites.